Automatic Sterilization Disinfection Fogging Using IoT Application System - Zulkefli, Noorfitriah; Mustafa, Mohamad Zaid; AHAD, ROSNEE (Research and Innovation in Technical and Vocational Education and Training, 2023)
Nowadays, humanizing a space or area is an important thing in life now. This Covid-19 contagion is of great concern to citizens, and the sanitary ware has become an important part of their lives. Therefore, this project can solve the problem by presenting a control system and monitoring a small space or area such as a house using only a smartphone. The development of this project is to centralize control units and switches to sanitize the space or area to be disinfected. The ESP2866 is used to interact with the hardware system. The Blynk app controls the system ON/OFF and pre-sets control times. So, users only need to open the system in their smartphone to set the time and status of the sanitation device. The project mainly focuses on a sanitation control system connected to the EPS2866 via a wireless router. In this project, a smartphone will act as a controller, a wireless router will serve as a medium between the connection, and the ESP2866 will act as a signal receiver.